The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/14759217211041002
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of self-healing in concrete with micro-capsules using a combination of air-coupled surface wave and computer-vision techniques

Abstract: This study mainly aims to investigate the applicability of the combination of air-coupled surface-wave and computer-vision techniques to the evaluation of self-healing in in situ concrete members. Small-scale beam specimens were made from ordinary concrete and concretes with solid- and liquid-type capsules; the capsules were employed as self-healing agents. To monitor the crack healing progress, surface-wave tests using an air-coupled transducer and contact receivers were conducted on each specimen in uncracke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Figure 15 shows the scanning electron microscopy (SEM) images of the healing products. It was observed that the healing products consisted of hexagonal crystals of calcium hydroxide and needle-like crystals of C-S-H [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 15 shows the scanning electron microscopy (SEM) images of the healing products. It was observed that the healing products consisted of hexagonal crystals of calcium hydroxide and needle-like crystals of C-S-H [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…), or material development properties. The most important wave-based methods for evaluating damages in structures made with concrete are: acoustic emission (AE) (Ospitia et al, 2023), impact echo (IE) (Fülöp et al, 2022), ultrasonic pulse velocity (UPV) (Revilla-Cuesta et al, 2022), surface-wave techniques (Lefever et al, 2022(Lefever et al, , 2023Ahn et al, 2018Ahn et al, , 2022aIn et al, 2015) and diffuse-wave techniques (Quiviger et al, 2012;Payan et al, 2013;In et al, 2017;Zhang et al, 2018;Ahn et al, 2022b) for monitoring and evaluation of healing, cracks or discontinuities in concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Comb transducers [12,13], electromagnetic acoustic transducers (EMATs) [14], interdigital transducers (IDTs) [15], and angle beam wedge transducers [16] are widely used in ultrasonic detection using Rayleigh waves. In addition, Rayleigh waves can also be generated when a piezoelectric (PZT) element rests on the edge of the sample [17], a point or line laser beam acts on the surface [18], an air-coupled transducer incidents wave obliquely to the solid surface [19], and an X-or Y-cut plate is located on the surface of the specimen [4]. In this work, the above transducers are grouped into two categories according to the type of excitation source.…”
Section: Introductionmentioning
confidence: 99%